Nitridation Temperature Effect on Carbon Vanadium Oxynitrides for a Symmetric Supercapacitor - Ndiaye, Ndeye M. (Nanomaterials (Basel), 2019)
In this work, porous carbon-vanadium oxynitride (C-V(2)NO) nanostructures were obtained at different nitridation temperature of 700, 800 and 900 °C using a thermal decomposition process. The X-ray diffraction (XRD) pattern of all the nanomaterials showed a C-V(2)NO single-phase cubic structure. The C-V(2)NO obtained at 700 °C had a low surface area (91.6 m(2) g(−1)), a moderate degree of graphitization, and a broader pore size distribution. The C-V(2)NO obtained at 800 °C displayed an interconnected network with higher surface area (121.6 m(2) g(−1)) and a narrower pore size distribution. In contrast, at 900 °C, the C-V(2)NO displayed a disintegrated network and a decrease in the surface area (113 m(2) g(−1)). All the synthesized C-V(2)NO yielded mesoporous oxynitride nanostructures which were evaluated in three-electrode configuration using 6 M KOH aqueous electrolyte as a function of temperature. The C-V(2)NO@800 °C electrode gave the highest electrochemical performance as compared to its counterparts due to its superior properties. These results indicate that the nitridation temperature not only influences the morphology, structure and surface area of the C-V(2)NO but also their electrochemical performance. Additionally, a symmetric device fabricated from the C-V(2)NO@800 °C displayed specific energy and power of 38 W h kg(−1) and 764 W kg(−1), respectively, at 1 A g(−1) in a wide operating voltage of 1.8 V. In terms of stability, it achieved 84.7% as capacity retention up to 10,000 cycles which was confirmed through the floating/aging measurement for up to 100 h at 10 A g(−1). This symmetric capacitor is promising for practical applications due to the rapid and easy preparation of the carbon-vanadium oxynitride materials.